THE EFFECT OF LEADERSHIP BEHAVIOUR AND REWARD SYSTEM ON THE EMPLOYEE PERFORMANCE MEDIATED BY ORGANIZATIONAL CITIZENSHIP BEHAVIOUR OF PT DANPAC PHARMA - Lavena, Ika; Singmin Johannes Lo (Dinasti International Journal of Management Science, 2020)
The purpose of this research is to understand and explain the effect of Leadership Behavior and Reward System on Employee Performance is mediated by Organizational Citizenship Behavior for Employees PT Danpac Pharma. The method used is quantitative approach, where the population in this study were 305 employees of PT Danpac Pharma. Engineering sample selection is done by taking a sample saturated to permanent employees as much as 146 respondents. Questionnaire survey instrument used data collection techniques and have been submitted to the employees of PT Danpac Pharma. Data of this study, which analyzed using structural equation models (SEM) 3.2.8 SmartPLS software program. This study reveaks that Leadership Behaviour and Reward System have a significant positive effect on Employee Performance mediated by Organizational Citizenship Behaviour both partially and simultaneously. In addition, the Leadership Behavior has a positive and significant effect on Organizational Citizenship Behavior and Reward System has a positive and significant effect on Organizational Citizenship Behavior. Leadership Behavior has a positive and significant effect on Employee Performance and Reward System has a positive and significant effect on Employee Performance.